EFEKTIFITAS PAKAN DARI BUNGKIL KELAPA SAWIT TERHADAP SINTASAN DAN PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - St Hadijah; Jayadi Jayadi; Harlina Harlina; Isya Nurkhaliza (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2019)
Tilapia (Oreochromis niloticus) including the Cichlidae family from Africa. Measuring 200 - 400 grams and omnivorous, it can consume vegetable and animal feed. Palm oil waste has a high enough protein so that it can be used as a source of vegetable protein in fish feed. This study aims to determine the effectiveness of palm oil waste feed on the survival rate, growth and feed conversion of tilapia. This study used a Completely Randomized Design (CRD) with the number of treatments 3 namely A = Palm Oil Dregs (POD) plus fine bran, B = POD plus fish meal, C = POD plus soy flour; with 3 replications. The parameters observed were survival, growth and Feed Convertion Rate (FCR). Stocking density for each tilapia 10 individuals / container. The results showed the survival of tilapia in treatments A and B gave the same results (86.66%) and treatment C (80%). The results of analysis of variance showed that the treatment did not significantly affect the survival of tilapia. The growth parameters, both in absolute growth and growth rates of tilapia during the study showed that the treatment had a significant effect on the growth of tilapia and the best treatment was treatment B, while treatments A and C were not significantly different. The FCR obtained was treatment A (1.27), B (1.18) and C (1.16). The results of variance analysis showed that the treatment had no significant effect on the tilapia FCR.